The Influence of Indonesian Language Management on Academic Communication and Campus Culture: A Case Study at Leading Universities in Indonesia to Improve the Quality of Learning - Ika Febriana; Wiko Prayoga; Jonathan Fransiscus Siringoringo; Willy Linchon Sihombing; Ahmad Suhendri Lubis; Aditia Warman Harahap (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the impact of Indonesian language management on academic communication and campus culture at a leading university in Indonesia, aiming to improve the quality of learning. Language management in higher education institutions plays a crucial role in fostering effective academic communication, creating a productive learning environment, and shaping a positive campus culture. Through a systematic literature review, this study examines existing language management strategies and their outcomes, evaluating the challenges and benefits they offer to the academic community. By highlighting best practices and potential improvements, this research provides valuable insights into the role of Indonesian language management in strengthening students' communication skills, cultural pride, and readiness for a professional environment.